Apakah Prosedur Pembersihan Kamar Tamu Diterapkan Pada Masa Pandemi Covid-19? Sebuah Studi Kasus - Ni Kadek Dwi Dharmayanti; Ida Ayu Sri Puspa Adi; I Wayan Sunarsa; Ni Ketut Iswarini (Program Studi Manajemen Divisi Kamar, 2022)
This study on the application of room cleaning procedures during the covid-19 pandemic at The Laguna, a Luxury Collection Resort & Spa Nusa Dua, Bali, aims to determine the application of room cleaning procedures during the covid-19 pandemic at The Laguna, a Luxury Collection Resort & Spa Nusa Dua, Bali. Data obtained from interview and documentation based on the application of room cleaning procedures during the covid-19 pandemic. Analysis of the data used by researchers is a qualitative descriptive technique. Qualitative descriptive technique is an analysis technique that first describes the existing problems and then compared in discussions referring to the Standard Operational Procedures and then comes to a conclusion. From the result of the study, it can be seen that the implementation of room cleaning procedures during the covid-19 pandemic at The Laguna, a Luxury Collection Resort & Spa Nusa Dua, Bali as a whole is in accordance with the Standard Operational Procedures that have been set. However, there are some points that have not been carried out optimally.